Characterization of antibiosis to the redbanded stink bug Piezodorus guildinii (Hemiptera: Pentatomidae) in soybean entries - Silva, Jose P. G. F. [UNESP]; Baldin, Edson L. L. [UNESP]; Souza, Efrain S. [UNESP]; Canassa, Vinicius F. [UNESP]; Lourencao, Andre L. (Springer, 2013)
Stink bugs are among the major pests of soybean [Glycine max (L.) Merrill] worldwide. Piezodorus guildinii [Westwood] (Hemiptera: Pentatomidae) is one of the predominant pest species, causing more severe damage in many regions than other stink bugs. Its attack reduces yield and quality of the beans. Plant resistance is a valuable strategy in integrated pest management that can reduce insect populations below economic injury level. Here, we report the resistance of 17 soybean entries to P. guildinii. PI 229358, PI 274454, L1-1-01, IAC 19, PI 171451, PI 227687, IAC 100, IAC 78-2318, PI 274453, and IAC 74-2832 caused high nymphal mortality (greater than 90 %), indicating the expression of antibiosis. IAC 100, IAC 74-2832, PI 274453, and IAC 24 also increased the length of the nymphal stage of P. guildinii, showing the same mechanism of resistance. Our findings may be useful for breeding programs that focus on the resistance of soybeans to insects.
Keywords: Host plant resistance; Redbanded stink bug; Antibiosis; Glycine max